Capsule endoscopy and enteroscopy: modern modalities to investigate the small bowel in paediatrics. Issue 2 (6th September 2007) - Sidhu, R; Sanders, D S; McAlindon, M E; Thomson, M
Abstract : Historically the small bowel has been considered a technically difficult area to examine because of its length (3-5 metres), location and tortuosity. Capsule endoscopy and enteroscopy have revolutionised the investigation pathway of the small bowel in adults. They are now developing increasingly important roles as modalities of investigation in paediatrics. This review appraises the current literature to define the clinical indications and practical aspects of capsule endoscopy and enteroscopy that are of interest to the clinician.